Inacoin Cryptocurrency Analysis: An Islamic Law Perspective - Windiastuti, Filka Catur; Athief, Fauzul Hanif Noor (Journal of Islamic Economic Laws, 2019)
The existence of money makes buying and selling activity easier than the barter system. However, the increasing globalization of the world economy demands speed accelaration, ease and security of financial transactions. The discovery of cryptocurrency provides solution for the current payment system which relies highly on the third party in conducting digital transactions. One of those cryptocurrency products is Inacoin which is originated from Indonesia. Because this cryptocurrency is a contemporary problem that cannot be concluded directly from the classical fiqh book, a thorough investigation is needed to obtain the validity of this money from Islamic perspective. This research is a qualitative research that uses multimethod of normative-empirical Islamic law perspective in discussing the aforementioned problem. This study concluded that the existence of Inacoin cannot be accepted as money since there are Islamic requirements or criteria that are not met. In addition, the use of Inacoin is mostly for trading commodity, not as money. The Inacoin trade is legitimate but unlawful, because Inacoin has fulfilled the pillars and requirements of the Al-?arf, yet contradicted some Islamic principal such as maisir, gharar, and possibility of harming its user